Monoclonal gammopathy of “ocular” significance - Karakus, Sezen (Am J Ophthalmol Case Rep, 2019)
PURPOSE: Diagnostic criteria for monoclonal gammopathy of undetermined significance (MGUS) do not currently include ocular phenotypic changes. Here, we offer a new diagnostic approach that is useful in patients with posteriorly located corneal depositions and present evidence to support the theory that the aqueous humor is a source for monoclonal proteins accumulated in the cornea. OBSERVATIONS: A 77-year-old woman presented to the clinic with a gradual decrease in visual acuity over 6 months. Slit lamp examination revealed bilateral central guttae consistent with Fuchs corneal dystrophy, peripheral circular band-like corneal opacities in the deep stroma, and bilateral nuclear sclerotic and cortical cataracts. Anterior segment optical coherence tomography confirmed corneal opacities in the posterior stroma and Descemet membrane. Immunological studies revealed increased serum IgG levels of 3220 mg/dL and serum electrophoresis showed an abnormal monoclonal band of 2.4 g/dL identified as IgG lambda by immunofixation electrophoresis. The patient was referred to the hematology clinic where she underwent further systemic workup and was diagnosed with MGUS. Immunofixation electrophoresis of aqueous sampling, which was performed at the time of cataract surgery, confirmed the presence of the IgG lambda gammopathy in the anterior chamber. CONCLUSIONS AND IMPORTANCE: Monoclonal gammopathy, although rare, should be included in the differential diagnosis of corneal opacities, as the ocular finding can be the initial manifestation of a systemic disease that can potentially be life-threatening. When corneal biopsy is not feasible due to the location of corneal pathology, aqueous sampling may be an alternative approach towards a clinical diagnosis. We propose a new terminology, “monoclonal gammopathy of ocular significance,” for patients diagnosed with MGUS, however, their only significant clinical finding is ocular manifestation.